2019
DOI: 10.3390/w11040860
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater Level Prediction for the Arid Oasis of Northwest China Based on the Artificial Bee Colony Algorithm and a Back-propagation Neural Network with Double Hidden Layers

Abstract: Groundwater is crucial for economic and agricultural development, particularly in arid areas where surface water resources are extremely scarce. The prediction of groundwater levels is essential for understanding groundwater dynamics and providing scientific guidance for the rational utilization of groundwater resources. A back propagation (BP) neural network based on the artificial bee colony (ABC) optimization algorithm was established in this study to accurately predict groundwater levels in the overexploit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 46 publications
(57 reference statements)
2
15
0
Order By: Relevance
“…The previous studies have indicated that the amount of groundwater recharge is maintained at approximately 31 million m 3 /year, while the total amount of exploitation is maintained at 40 million m 3 /year in Yaoba Oasis [46]. Although the groundwater level slowly recovers during the year, the recharge cannot still meet the exploitation, resulting in the gradual decline in groundwater level year after year.…”
Section: Dynamic Characteristics Of Annual Groundwater Levelmentioning
confidence: 99%
“…The previous studies have indicated that the amount of groundwater recharge is maintained at approximately 31 million m 3 /year, while the total amount of exploitation is maintained at 40 million m 3 /year in Yaoba Oasis [46]. Although the groundwater level slowly recovers during the year, the recharge cannot still meet the exploitation, resulting in the gradual decline in groundwater level year after year.…”
Section: Dynamic Characteristics Of Annual Groundwater Levelmentioning
confidence: 99%
“…On the other hand, machine learning-based models as statistical approaches have shown the great capability for simulating and forecasting of complicated phenomena. These techniques have been successfully applied to forecasting purposes for a large number of real-world applications such as river flow forecasting and hydrological modeling [4][5][6][7], water quality predictions [8][9][10], and groundwater level estimations [11][12][13], etc. Detailed descriptions of big data in complex and social networks are presented in [14].…”
Section: Introductionmentioning
confidence: 99%
“…Groundwater level is an indicator of groundwater availability, groundwater flow and the physical characteristics of an aquifer or groundwater system (Nair and Sindhu 2016). A decrease in groundwater levels can trigger a number of eco-environmental problems capable of seriously affecting both local agricultural production and economic development (Li et al 2019). Groundwater level is an important indicator of groundwater balance.…”
Section: Introductionmentioning
confidence: 99%
“…Influence of climatic factors and human activities can make groundwater level exhibits cyclical and random characteristics. Therefore, the accurate prediction of groundwater level is of great significance for the rational utilization of groundwater resources and the sustainable development of the social economy (Li et al 2019).…”
Section: Introductionmentioning
confidence: 99%